Mapping the Intellectual Landscape of Local Wisdom-Based Learning: A Bibliometric Analysis - Yuli Untari; Abdul Hafid; Teguh Yuliandri Putra; Mursalim Mursalim; Sri Rizki Handayani (Pedagogia: Jurnal Ilmiah Pendidikan, 2026)
This study aimed to systematically map global research trends, intellectual structures, and collaborative dynamics concerning the integration of local wisdom into education for fostering student creativity. A descriptive bibliometric approach combined with qualitative content analysis was employed. A refined dataset of 3,057 peer-reviewed articles published between 2017 and 2025 was retrieved from the Dimensions database following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Bibliometric mapping and network visualization were conducted using VOSviewer to examine publication growth, citation patterns, keyword co-occurrence, thematic evolution, and research density. The findings revealed an exponential increase in annual publications and cumulative citations, indicating growing scholarly interest in integrating local wisdom into educational research. Network visualization identified “local wisdom” as the central keyword, strongly connected with science learning, character education, and student creativity. Overlay visualization demonstrated a shift from conceptual discussions toward empirical investigations emphasizing classroom implementation and educational impact. Density mapping further revealed thematic disparities, showing extensive attention to general student contexts, whereas specific learning processes, cognitive mechanisms underlying creativity, and empirical evaluations of instructional effectiveness remain underexplored. This study provides a comprehensive bibliometric baseline that captures the evolution of local wisdom-based education and identifies emerging research opportunities. The findings offer valuable directions for future investigations and support the development of culturally responsive and sustainable educational innovations that strengthen creativity and improve instructional quality across diverse learning contexts.